Usefulness of antenatal care handbook: a cross-sectional study of mothers' perspectives - Queenita Anak Luta; Khadizah Haji Abdul Mumin; Hanif Abdul Rahman; Sarena Haji Hashim (PAGEPress Publications, 2023)
In 2016, the Ministry of Health Brunei Darussalam introduced the Maternal and Child Health (MCH) Handbook, replacing the card-type record. Despite its implementation, the handbook's utility remains unexamined. This study aims to evaluate the community's usage of the MCH handbook and explore the connections between age, education, and handbook utilization. A cross-sectional study employed an online self-administered survey among pregnant women attending routine antenatal checkups at 32 weeks gestation between December 2020 and January 2021. The survey used the MCH Usefulness Questionnaire, and subgroup analysis was conducted. The study included 73 mothers. Most participants reported having sufficient time to read the handbook (95.9%), being familiar with its content (89.0%), and feeling satisfied with its usage (93.2%). Reasons for not using the handbook included "online availability of the same information" (20.5%), difficulty in understanding certain words (17.8%), preference for more visual content (12.3%), and inadequate encouragement from healthcare providers (12.3%). The majority of mothers perceive the handbook as useful. Nonetheless, further investigation is necessary to delve into their perceptions and ensure the handbook's sustained relevance and effectiveness over time.